1997
DOI: 10.1093/jmedent/34.3.321
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to Bacillus sphaericus Involves Different Mechanisms in Culex pipiens (Diptera: Culicidae) Larvae

Abstract: Field Culex pipiens pipiens (L.) mosquitoes that were collected after a control failure with Spherimos in southern France developed high resistance (> 10,000-fold) to Bacillus sphaericus crystal toxin after < 8 generations of laboratory selection. We show that this resistance is encoded by a single major recessive gene on linkage group I at 22.1 recombination units from the sex locus, and that it is not associated with any loss of binding affinity between brush border membrane fractions and the B. sphaericus r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
47
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(50 citation statements)
references
References 9 publications
2
47
1
Order By: Relevance
“…The mechanisms of resistance to B. sphaericus are not yet defined (46,47), but more than one mechanism seems to be involved (48). Resistance to B. thuringiensis has resulted from reduced binding of the toxin to the brush border in the lumen of the insect gut (49,50) or by enhanced digestion of toxin by gut proteases (51).…”
Section: Resistance To Growth Regulators Ivermectins and Other Micrmentioning
confidence: 99%
“…The mechanisms of resistance to B. sphaericus are not yet defined (46,47), but more than one mechanism seems to be involved (48). Resistance to B. thuringiensis has resulted from reduced binding of the toxin to the brush border in the lumen of the insect gut (49,50) or by enhanced digestion of toxin by gut proteases (51).…”
Section: Resistance To Growth Regulators Ivermectins and Other Micrmentioning
confidence: 99%
“…Disruption of the interaction between the toxin and the midgut is the major mechanism underlying resistance, and it has already been reported from different laboratory-or fieldselected colonies (25,26,27,33). Unrelated mechanisms may also be involved in resistance, but they have not been characterized so far (25,27).Molecular studies revealed that mutations in the genes cpm1 and cqm1, which prevent the production of functional membrane-bound receptors, are the main reasons behind the lack of binding of the Bin toxin to the midgut epithelium. Four cpm1/cqm1 resistance alleles were found in Culex populations of different origins.…”
mentioning
confidence: 98%
“…The action of the Bin toxin on Culex larvae relies on its specific binding to those membrane-bound receptors (24). Disruption of the interaction between the toxin and the midgut is the major mechanism underlying resistance, and it has already been reported from different laboratory-or fieldselected colonies (25,26,27,33). Unrelated mechanisms may also be involved in resistance, but they have not been characterized so far (25,27).…”
mentioning
confidence: 99%
“…The following three susceptible and four resistant colonies of C. pipiens pipiens and C. pipiens quinquefasciatus were investigated in this study: (i) JRMM-R, a laboratory-selected field colony of C. pipiens quinquefasciatus with fivefold resistance, and its parental susceptible colony, JRMM-S (F-S and F-SEL, respectively) (25,26); (ii) KOCHI, a C. pipiens quinquefasciatus colony with high-level (Ͼ2,000-fold) resistance to B. sphaericus that was field selected from an area of southern India treated with B. sphaericus strain 1593M (22), and Madurai, a susceptible laboratory colony of C. pipiens quinquefasciatus; (iii) SPHAE, a C. pipiens pipiens colony with high-level (Ͼ50,000fold) resistance that was generated by field selection from an area of southern France treated with B. sphaericus strain 2362 (16,33); and (iv) GeoR, a C. pipiens quinquefasciatus colony with high-level (Ͼ50,000-fold) resistance that was produced by G. P. Georghiou, who selected field-collected larvae from California with B. sphaericus 2362 in the laboratory (15,36). The SPHAE and GeoR colonies were established from egg rafts kindly provided by Nicole Pasteur (University of Montpellier II, Montpellier, France) (SPHAE) and by G. P. Georghiou and Margareth Wirth (University of California, Riverside) (GeoR) and were reared at the Pasteur Institute in the Entomopathogenic Bacteria Unit.…”
Section: Methodsmentioning
confidence: 99%
“…Levels of stable laboratory-selected resistance of between 35-fold and more than 100,000-fold have been reported, suggesting that there may be different resistance mechanisms. Investigations of the mechanisms and genetics of resistance to B. sphaericus have been carried out for some of the resistant populations (15,16,36).…”
mentioning
confidence: 99%